Serum levels of interleukin-6 type cytokines and soluble interleukin-6 receptor in patients with rheumatoid arthritis. Issue 5 (1998) - Robak, T.; Gladalska, A.; Stepień, H.; Robak, E.
Abstract : We investigated the serum concentrations of interleukin-6 (IL-6) and two IL-6 family of cytokines (leukaemia inhibitory factor (LIF) and ciliary neurotrophic factor (CNTF) as well as IL-6 soluble receptor (sIL-6R) using an enzyme-linked immunosorbent assay (ELISA) in 66 patients with rheumatoid arthritis (RA) and 24 healthy controls. We examined a possible association between the serum levels of these peptides and RA activity according to the Mallya and Mace scoring system and Ritchie's index. We also evaluated the correlation between the serum levels of IL-6, LIF, CNTF and sIL-6R and duration of the disease and calculated sIL-6R/IL-6 ratio in RA patients and in the control group. IL-6 and sIL-6R were detectable in all 66 patients with RA and 24 normal individuals. LIF was also found in the serum of all patients with RA and in 16 (66.7%) normal individuals. In contrast CNTF was measurable only in 15 (22.7%) patients with RA and 24 (33.3%) normal individuals. The highest IL-6 and sIL-6R levels were found in the patients with Stages 3 and 4 of RA activity and the lowest in the control group. In contrast there were no statistically significant diferences between the LIF and CNTF levels in RA patients and normal individuals. We found positive correlation between IL-6 and sIL-6R concentrations and Ritchie's index and a lack of such correlation with LIF and CNTF. IL-6 serum level correlated positively with the disease duration, but sIL-6R, LIF and CNTF did not. Serum sIL-6R/IL-6 ratio was significantly lower in RA patients than in healthy controls. In conclusion, an increase in the serum levels of IL-6 and sIL-6R, but not LIF and CNTF concentrations, may be useful markers for RA activity.